Tradice spojená s oslavami Nového roku: Židovská komunita v Praze - Segerová, Vendula (Lidé města, 2003)
The New Year celebration is an important part of the Jewish calendar and also in modem society. This study deals with the New Year, its formal celebration, liturgy and reflection of the liturgy as a part of a Jewísh identity. It also deals with the celebratíon in the family and friends in the Prague Jewish community. The beginning briefly describes the current climate of the Prague Jewish community. Reestablishment of religious life is typical for the end of 20th and beginning of the 21st century. The life of the community without the religious aspects is reestablished as well. The study continues with describing the New Year by the halachic (religious law) standarts. The New Year is celebrated over two days - the 1. and the 2.of Tishri (September or October). The year 2001/2002 corelates to the Jewish year of 5762 which is counted since the creation of man. The New Year is connected with many special traditions - especially at home; for example: eating symbolic foods (honey, carrot, dates, fish ...), shofar blowing, tashlich etc. What follows is the discussion of the New Year in the Prague Jewish community. There is celebrating in the synagogue, at home, preparing for Yom Kippur. Prague has seen a reestablishment of the tradition that was interrupted by the shoa and forty years of the communist period. Most of the members of the community feel they do not need the New Year celebration to define their self-identity.